Processus de construction d’une ressource territoriale valorisant le patrimoine naturel et culturel en Loire tourangelle - Benoit Pin; Sylvain Rode; Sylvie Servain (VertigO)
The listing of the “Val de Loire” on the Unesco list of World Heritage realized the emergence of new representations of the Loire heritage and promoted local development projects mobilizing it. Despite its international recognition, the Loire heritage is not appropriate in its entirety by the local population. Different visions of heritage confront each other, materializing as much sensitivities as public policy and civil society influences on representations. First of all, this work attempts to put in light the built character of the patrimonial landscape. In a second time, it wants to present why and how this heritage is mobilized as a resource for local development projects. The analysis is conducted across two main municipalities (Bréhémont and Chouzé-sur-Loire) which are involved in processes of heritage valorization. It is supplemented by analyzes conducted across a stretch of the Loire (from Tours to the confluence of the Loire and Vienne) in way to put into perspective the realities on the ground of the heritage valued by local development projects.